Transnationalising Jamaah Islamiyyah - Zuhri, Syaifudin (Al-Jamiah Research Centre, 2010)
This article attempts to historically analyse the emergence of transnational jihadist movements in Indonesia, focusing on Jamaah Islamiyyah (JI), which is allegedly responsible for a number of terror attacks in South East Asia.Â The article discusses the historical background of the emergence of JamaahÂ Islamiyyah and its current development. It is argued that the Afghan battle-field was an important event and locus for Indonesian jihadits groups to exercise their military capabilities, establish secure bases and subsequently pave the emergence of the transnational jihadist. Through informal networks and joint operations, Jamaah Islamiyyah has become the hub for jihadist movementsÂ in Southeast Asia. It was the political opportunity of the reformation which gave way to the public appearance of Jamaah Islamiyyah as the MMI demonstrated, but it also brought the consequence of a split among JI activists.Â The split reappears when the MMI was becoming involved in politics, and the resignation of Baâasyir from the top position of the MMI in 2008 exemplifiesÂ the turning point to the ideological foundation of JI as the Pedoman Umum Perjuangan Jamaah Islamiyyah (PUPJI) prescribed.